Simplifying radicals numbers
Simplify √45
3√5
√(x+2)=3
x=7
x2 = 121
x=11
(t4)(3t7)
3t11
(k3)5
k15
Simplify √75
5√3
7+√(9x-2)=12
x=3
2x3 - 7 = 9
x = 2
(7x7)(4x3)
28x10
(2x3)4
16x12
Simplify 2√12
4√3
4√(2y-1)-2=10
y=5
-10+√3x = -1
x=27
(4m4n2)(3m5n3)
12m9n5
(5xy4)3
125x3y12
Simplify √384
8√6
5x3 - 10 = 54
x=2
3(x-2)2=27
x=5
(x5y2z4)(2x3y2z4)(4x3)
8x11y4z8
(32x5y2)2
81x10y4
Simplify -7√96
-28√6
3(x-2)2 - 11 = 1
x=4
6(5x+2)2 - 3 =36
x=1/5 or 0.2
(3x4y3z2)(8x5y4z3)(5x2)
120x11y7z5
(4a5b3c2)3
64a15b9c6